PERENCANAAN GEDUNG MESS 5 LANTAI PEKERJA PABRIK PT. PARKLAND WORLD INDONESIA (PWI) DI MAYONG JEPARA. - Prasetya, Hendryk Ratna; Hidayati, Nor; Rochmanto, Decky (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2023)
The development of the industrial revolution has an impact on economic growth that is increasingly evenly distributed throughout Indonesia, not least in Jepara Regency, especially in industrial areas that have been provided by the government, but the limited land available has an impact on the increasing number of tall buildings being built to support housing needs in the surrounding area.In the construction of multi-storey buildings, careful planning is needed so that the building structure is able to stand strong, withstand earthquakes, be efficient and meet SNI. Careful planning will avoid the occurrence of building failures or unwanted construction failures.In this final project the building being reviewed is a 5-story building which is a 5-story mess building for factory workers of PT. Parkland World Indonesia in Mayong Jepara, The calculation of the structure of the building is reviewed against dead loads, live loads and earthquake loads using SAP 2000. The calculations include roofs, plates, beams, columns, and foundations. The planning location of the building is on Jl. Raya Jepara - Kudus, Pelang, Kec. Mayong, Jepara Regency, Central JavaFrom the planning obtained a concrete structure with a thickness of 120 mm 12 - 200 slab, beam 400 x 800 mm 9 D19, 300 x 600 mm 8 D12, 200 x 400 mm 7 D12. column 500 x 750 mm 12 D19, and 500 x 500 mm 8 D19, with concrete quality (f'c) = 30 MPa, deform reinforcement quality (fy) = 400 MPa and plain reinforcement quality (fy) = 240 MPa. the roof structure uses double angel steel truss 2L.40.40.3 and 2L.30.30.3, the lower structure uses 6 m long piles with a diameter of 40 cm.